EVALUATION OF SLOW DEEP BREATHING TECHNIQUE ON PAIN SCALE IN POST-SURGICAL PATIENTS - Hilaria Erika; Fransiska Anjar Rina Setyani; Fittriya Kristanti (Jurnal Keperawatan Sriwijaya, 2026)
Aim: This study aimed to evaluate the slow deep breathing technique on pain scores in post-surgical patients. Methods: The study used a quasi-experimental design with a pretest and posttest approach, with a control group. A sample size of 48 respondents, consisting of 24 in the intervention group and 24 in the control group, was selected using accidental sampling according to inclusion criteria. Pain intensity was measured using a visual analog scale before and after the intervention. The intervention group was given the slow deep breathing technique once for ten minutes, while the control group received no special treatment. Data were analyzed using the Mann-Whitney test to determine differences in pain scores between the two groups. Results: Based on the study results, the intervention group experienced a decrease in the average pain score after administering the Slow Deep Breathing (SDB) technique compared to before the intervention (p = 0.000). Similarly, the control group saw a decrease in the average pain score between the pre- and post-observation measurements (p = 0.004), although the magnitude of the decrease was smaller than that of the intervention group. Conclusion: This study concluded that there was no significant difference in post-surgical pain reduction between the intervention group receiving the slow deep breathing technique and the control group. The slow deep breathing technique can still be considered a supportive non-pharmacological intervention in pain management. Future research is recommended to optimize the frequency and duration of interventions and consider environmental factors and surgical characteristics that may influence patient pain perception.